News from the PUB: plant U-box type E3 ubiquitin ligases. (10th December 2017) - Trujillo, Marco
Abstract : Plant U-box type E3 ligases are linked to major signalling pathways and engaged in a wide array of functions to control cellular homeostasis. Abstract: Plant U-box type E3 ubiquitin ligases (PUBs) are well known for their functions in a variety of stress responses, including immune responses and the adaptation to abiotic stresses. First linked to pollen self-incompatibility, their repertoire of roles has grown to encompass also the regulation of developmental processes. Notably, new studies provide clues to their mode of action, underline the existence of conserved PUB–kinase modules, and suggest new links to G-protein signalling, placing PUBs at the crossroads of major signalling hubs. The frequent association with membranes, by interacting and/or targeting membrane proteins, as well as through a recently reported direct interaction with phospholipids, indicates a general function in the control of vesicle transport and their cargoes. This review aims to give an overview of the most significant advances in the field, while also trying to identify common themes of PUB function.